Temperature Significantly Affects the Plaquing and Adsorption Efficiencies of Listeria Phages - Tokman, Jeffrey I.; Kent, David J.; Wiedmann, Martin; Denes, Thomas (Frontiers in Microbiology, 2016)
Listeria-infecting phages are currently being used to control and detect the important foodborne pathogen Listeria monocytogenes; however, the influence of environmental conditions on the interactions between L. monocytogenes and its phages has not been explored in depth. Here, we examined the infective potential of four Listeria phages (two each from the P70-like and P100-like phages of Listeria) against five strains of L. monocytogenes (representing serotypes 1/2a, 1/2b, 4a, and 4b) grown under a range of temperatures (7ºC – 37°C). We show that the plaquing efficiencies for all four phages were significantly affected by temperature. Interestingly, no plaques were observed for any of the four phages at 37°C. Adsorption assays performed with the P100-like phages, LP-048 and LP-125, showed that LP-048 had a severely reduced adsorption efficiency against susceptible strains at 37°C as compared to 30°C, suggesting that there is considerably less accessible rhamnose (LP-048’s putative phage receptor) on the host at 37°C than at 30°C. LP-125 adsorbed to host cells at 37ºC, indicating that the inability for LP-125 to plaque at 37°C is not due to adsorption inhibition. LP-048 showed significantly higher adsorption efficiency against a mutant strain lacking N-acetylglucosamine in its wall teichoic acids than the parental strain at both 30°C and 37°C, suggesting that N-acetylglucosamine competes with rhamnose for glycosylation sites on the wall teichoic acids. The data presented here clearly shows that L. monocytogenes can gain physiological refuge from phage infection, which should be carefully considered for both the design and implementation of phage-based control and detection applications.